The effect of using grain collage media on the development of fine motor skills in children aged 5-6 years - Siregar, Ronni Naudur; Simanjuntak, Netti Meilani; Purba, Agnes (International Journal of Health Science and Technology, 2025)
According to World Health Organization (WHO) data, 5–25% of preschool-aged children have mild brain dysfunction, such as fine motor impairments, which is a common cause of preschool developmental failure.  According to data from the United Nations Children's Fund (UNICEF), up to 1,375,000 out of every 5 million toddlers had both fine motor and gross motor developmental impairments. The capacity to move smoothly is known as fine motor development, and it has an impact on cognitive development. This study aims to determine the effect of grain collage media stimulation on the fine motor development of children aged 5-6 years at Kharis Kids Tanjung Gusta Kindergarten in 2023. This type of research is a pre-experiment with a one group pretest-posttest design. The population in this study were all students at Kharis Kids Tanjung Gusta Kindergarten aged 5-6 years as many as 20 students in the 2023 Academic Year who will be studied, the sampling technique used was Total Sampling. The research instrument used KPSP (Pre-Screening Development Questionnaire) which was assessed before and after grain collage stimulation on the picture pattern. The results of the study showed that the Wilcoxon statistical test revealed a significant value of 0.001 (p-value <0.05). This study discovered that children's fine motor development was significantly impacted by the use of grain collage.  It is expected that parents of children between the ages of five and six will be able to keep an eye on their development in accordance with their age in order to optimize their health.